2014
DOI: 10.3109/21681805.2014.971426
|View full text |Cite
|
Sign up to set email alerts
|

Upper urinary tract retroperitoneoscopic surgery under epidural anesthesia: Shifting towards outpatient treatment

Abstract: Retroperitoneoscopy for benign upper tract pathology combined with epidural anesthesia is a feasible and an attractive method for both surgeon and patient. No postoperative pain and early recovery are the most beneficial results of this technique. Further studies, applying this technique in patients with cardiopulmonary problems, should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…This minimally invasive technique is associated with quicker recovery and fewer complications, making the short-term result of retroperitoneoscopic surgery apparently superior to open surgery. 9,18,19 In our study, the mean surgery time of RNU was slightly longer than that of ONU, but the difference was not statistically significant. Our surgical experience has indicated that the key factor to influence surgical time is how quickly the renal artery is identified.…”
Section: Discussioncontrasting
confidence: 71%
“…This minimally invasive technique is associated with quicker recovery and fewer complications, making the short-term result of retroperitoneoscopic surgery apparently superior to open surgery. 9,18,19 In our study, the mean surgery time of RNU was slightly longer than that of ONU, but the difference was not statistically significant. Our surgical experience has indicated that the key factor to influence surgical time is how quickly the renal artery is identified.…”
Section: Discussioncontrasting
confidence: 71%
“…Generally, the procedure is carried out under general anesthesia, although other anesthesiologic techniques for mini-invasive surgery such as spinal and epidural anesthesia are under investigation. 15,16 The transperitoneal approach is usually favoured because of its more familiar anatomic landmarks and larger working area, although the retroperitoneal route is also feasible.…”
Section: Robotic-assisted Laparoscopic Pyeloplastymentioning
confidence: 99%
“…In surgeries that must be done with general anesthesia, epidural anesthesia can be used for the maintenance of anesthesia or in the postoperative period. In this way, the rate of intraoperative complications can be reduced and patients' comfort can be increased by providing postoperative pain control and also duration of hospital stay can be reduced [1].© 2017 The Author(s). Licensee InTech.…”
mentioning
confidence: 99%